Investigation on the hyperledger blockchain - Zheng, Nini (Nanyang Technological University, 2021)
Blockchain technology is one of the popular internet database technologies. It is characterized by decentralization, openness and transparency, immutability and security. There are serval kinds of blockchain network which are public, permissioned and so forth. And this report is based on Hyperledger fabric. Blockchain technology has many problems when applying it to different situations. Compared with public blockchain, the transaction speed of the private blockchain is faster because of the limitation of access. However, when more nodes have been created in private blockchain, the more instability of the performance appear. There are many risks such as Non-determinism Arising from Language Instructions, Non-determinism Caused from Accessing Outside of Blockchain and so forth. Not good enough performance for many transactions is one of the problems. This report aims to improve the performance of Hyperledger Fabric. Hyperledger Fabric has four phases which are simulation phase (endorsing phase), ordering phase, validation phase and commit phase. I have done theorical research on the latency in three phases of fabric and two optimizations for decreasing the latency and increasing the throughput. As well, I have performed the sample test for latency using Hyperledger Caliper. I am trying to test the first-network performance in additional.